![if \ \textless \ br /\ \textgreater \ \frac{a}{x + y } \: = \frac{b}{y + z} = \frac{c}{z - x} \\ \ \textless \ br /\ \textgreater \ then \: show \: that \: b = a + c if \ \textless \ br /\ \textgreater \ \frac{a}{x + y } \: = \frac{b}{y + z} = \frac{c}{z - x} \\ \ \textless \ br /\ \textgreater \ then \: show \: that \: b = a + c ](https://tex.z-dn.net/?f=if+%5C++%5Ctextless+%5C+br+%2F%5C++%5Ctextgreater+%5C+%5Cfrac%7Ba%7D%7Bx+%2B+y+%7D+%5C%3A+%3D+%5Cfrac%7Bb%7D%7By+%2B+z%7D+%3D+%5Cfrac%7Bc%7D%7Bz+-+x%7D%C2%A0+%5C%5C+%5C++%5Ctextless+%5C+br+%2F%5C++%5Ctextgreater+%5C+then+%5C%3A++show++%5C%3A+that+%5C%3A++b+%3D+a+%2B+c+%E2%80%8B)
Answers
Answered by
9
Answer:-
Given:-
Prove That :-
Solution:-
Then, we get
↦
By doing cross multiplication we get,
➦
↦
By doing cross multiplication we get,
➦
And,
↦
By doing cross multiplication we get
➦
Hence, we get the value of a , b and c :
→a = k(x + y)
→b = k(y + z)
→c = k(z - x)
Then,
By putting the value of a , b and c we get,
⇒
⇒
➠
Similar questions